9+3q=12+2q

Simple and best practice solution for 9+3q=12+2q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+3q=12+2q equation:


Simplifying
9 + 3q = 12 + 2q

Solving
9 + 3q = 12 + 2q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-2q' to each side of the equation.
9 + 3q + -2q = 12 + 2q + -2q

Combine like terms: 3q + -2q = 1q
9 + 1q = 12 + 2q + -2q

Combine like terms: 2q + -2q = 0
9 + 1q = 12 + 0
9 + 1q = 12

Add '-9' to each side of the equation.
9 + -9 + 1q = 12 + -9

Combine like terms: 9 + -9 = 0
0 + 1q = 12 + -9
1q = 12 + -9

Combine like terms: 12 + -9 = 3
1q = 3

Divide each side by '1'.
q = 3

Simplifying
q = 3

See similar equations:

| 11v-9v=4 | | 70-3x=90-11x | | (9x+12y)(9x-12y)= | | (Y-5)+x=2.5y | | 5(c-4)=6(c-5) | | log(x)-log(x+11)=-1 | | 3m-29=-44+8m | | 5(x+10)=7x-32 | | 4800000=2900000+1600x | | 3x^2+32x+20= | | -20-2x=-30 | | 6m-5=-23+9m | | -30=-84 | | 5y-4+y+30=8y+30-4y | | 3(3x+7)-7=18x+1-9x | | 2[3(X+y)-4(6x-5y)]= | | 6m-5=23+9m | | -(x-7y)-2(2y-5x)=0 | | 3(x+3)-2=3x+2 | | 3x(x^3+6)= | | 20x+25x=180 | | Y=-x+3y | | 3(b+7)=-3 | | -20-2x=30 | | 4756505=2896112+1600x | | 2(x-3)=27 | | 5-4x=4x | | 10n-40=15n+15 | | 3p-3=4(p+1)-p | | 2x+3x-5x+x=42 | | 21=9x+1-5x | | 4(3x-6)=-60 |

Equations solver categories